The Thunderbolt of Evil and Goodness without Witnesses: In Conversation with Vasili Grossman, Life and Fate - Anckaert, Luc (Religija ir kultūra, 2016)
[full article, abstract in English; abstract in Lithuanian] The reviled Jewish-Russian war correspondent Vasily Grossman wrote a masterful novel Life and Fate about the historical battle of Stalingrad (1943), in which he sharply fillets both the Nazi and Stalinist forms of terror in a literary style. The great ideas about society lead to abuse of power and to oppression. Against the common ideals, Grossman argues for a form of small goodness that takes place on the concrete intersubjective plane. In this article, I elucidate the literary ideas of Grossman by confronting them with analogous philosophical approaches. First of all, the connection between modern rationality and a concentration camp is discussed. Both are accompanied by a form of thoughtlessness. The different forms of small goodness are then analyzed: the refusal to be complicit, the criticism of the great ideologies, the self-sacrifice, the deviation from the command, and the usual ethical norms. For Grossman, the possibility of ethics distinguishes man from the surrounding world. Humanity will remain as long as people are capable of the small goodness.